THE TEACHER: AUTHORITY, LEADER OR TRAINING MODEL FOR THE PERSONALITY OF THE STUDENTS IN THE PRIMARY CLASSES - Nicolae SILISTRARU; Carmen BUNDA (Acta et Commentationes, Sciences of Education, 2020)
Teachers have more basic roles in their activity so as: planning, organizing, controlling and guiding the assessment, counseling, educational decision. The teacher`s personality must involve the quality of being authoritative, good leader and a model; all these qualities should be harmonious. The teacher acts as a model in all situations, regardless of his will, and regardless of the fact that the student takes positive or negative elements from his teacher's behavior. In this context, the teacher has to manage both the direct elements of his behavior as well as the indirect ones.